Mapping the Topic Landscape of JPIM, 1984–2013: In Search of Hidden Structures and Development Trajectories1. Issue 6 (29th October 2015) - Antons, David; Kleer, Robin; Salge, Torsten Oliver
Abstract : During the three decades since its inception in 1984, the JPIM has shaped the evolution of innovation research as a scientific field. It helped create a topic landscape that is not only more diverse and rich in insights, but also more complex and fragmented in structure than ever before. We seek to map this landscape and identify salient development trajectories over time. In contrast to prior citation‐based studies covering the first two decades of JPIM research, we benefit from recent advances in natural language processing and rely on a topic modeling algorithm to extract 57 distinct topics and the corresponding most common words, terms, and phrases from the entire full‐text corpus of 1008 JPIM articles published between 1984 and 2013. Estimating the development trajectory of each topic based on yearly publication counts in JPIM allows us to identify "hot, " "cold, " "revival, " "evergreen, " and "wall‐flower" topics. We map these topics onto the Product Development and Management Association (PDMA) Body of Knowledge categories and discover that these categories differ significantly not only in terms of their internal topic diversity and relative prevalence, but also—and arguably more importantly—in terms of their publication and citation trajectories over time. For instance, the PDMA category "Codevelopment and Alliances" exhibits only moderate topic diversity (7 out of 57 topics) and prevalence in JPIM (161 out of 1008 articles). That said, it is among the most dynamic categories featuring two evergreen topic ("Users and Innovation" and "Tools and Systems for Technology Transfer") and three hot topics ("Open Innovation, " "Alliances and Cooperation, " and "Networks and Network Structure") as well as a sharply growing annual number of citations received. Our findings are likely to be of interest to all those who are keen to (re)discover JPIM 's topic landscape in search of hidden structures and development trajectories.